CC-CBTA-Based Floating Inductance Simulator with CM/VM PID Controllers - Sagbas, M.; Taskiran, Z. G. Cam; Ayten, U. E. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2024)
This work describes voltage-mode (VM), current-mode (CM) PID controllers and an electrically controllable floating inductance (FI) simulator circuit. Only a single current-controlled current backward transconductance amplifier (CC-CBTA) and a grounded capacitor are used in the proposed FI simulator circuit. One CBTA, one CC-CBTA, two capacitors and one resistor are used in the proposed PID controllers. All of the proposed circuits have appropriate input and output impedance values, allowing them to be utilized in cascade connections without requiring a buffer circuit. There is also no matching constraint between the active and passive values of the proposed circuit. The SPICE software environment and experimental results were used to validate theoretical derivations and associated outcomes. The layout of the CC-CBTA has been built, and the post-layout simulations are carried out using the netlist extracted from the layout. Comparisons were made with similar circuits found in the professional literature.
Keywords: Current-mode circuits; inductor simulators; analog circuits; PID controllers; current backward transconductance amplifier; Computer Science; Engineering